Indikasi dan Kontraindikasi Pemberian Fibrinolisis pada Pasien ST Elevation Myocardial Infarction Anterolateral Inferior (STEMI) dengan Syok Kardiogenik: Studi Kasus - Sari, Galuh Puspito; Kosim, Maryami Yuliana; Prananingrum, Febriana (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2024)
Background: Cardiogenic shock is a complication of STEMI. Fibrinolytic reperfusion is one of the revascularization modalities to prevent death in patients with STEMI. Currently, there is no information regarding the indications and contraindications for cardiogenic shock patients.Objective: To know the indications and contraindications for fibrinolysis in STEMI patients with cardiogenic shockCase report: A patient who was diagnosed with STEMI, came to the emergency room at RSA UGM. He felt pain in the left side of the chest which was felt like VAS 8 and persisted for 30 minutes but it did not spread to the back, show shortness of breath, or cold sweat. Acral cold, blood pressure 96/50 mmHg, pulse 92/minute. Diagnosis of anterolateral et inferior STEMI, initial management of STEMI was given and reperfusion therapy was planned.Outcome: There was a decrease in blood pressure of 88/52 mmHg with MAP 62 mmHg pulse of beats per minute. The patient was given support a dobutamine drip 5mcg/kg/min and then pro referred to RSUP Dr Sardjito for primary PCI due to cardiogenic shock. Based on considerations of cardiogenic shock that occurred in the patient, fibrinolysis therapy was not chosen because the results would not be effectived due to low aortic pressure. The low pressure will interfere with the delivery of fibrinolytic agents.Conclusion: STEMI with cardiogenic shock adds clinical complexity to the patient. Fibrinolysis is not effective in patients with cardiogenic shock. Thus, primary PCI becomes the best choice of theraphy for STEMI patient. In conclusion, cardiogenic shock is a contraindication for fibrinolytic reperfusion.INTISARILatar belakang: Syok kardiogenik merupakan komplikasi STEMI. Reperfusi fibrinolisis adalah salah satu modalitas revaskularisasi untuk mencegah kematian pada pasien dengan kasus STEMI. Saat ini, belum ada informasi tentang indikasi dan kontraindikasi pada pasien syok kardiogenik.Tujuan: Untuk memahami indikasi dan kontraindikasi fibrinolisis pada pasien STEMI dengan syok kardiogenik.Laporan kasus: pasien datang ke IGD RSA UGM dengan keluhan nyeri dada sebelah kiri, terasa seperti tertindih, VAS 8 menetap sejak 30 menit, tidak menjalar sampai ke punggung, sesak napas, dan keringat dingin. Akral pasien teraba dingin, tekanan darah 96/50 mmHg, nadi 92x/menit. Diagnosis pasien STEMI anterolateral et inferior, diberikan penatalaksanaan awal STEMI dan direncanakan terapi reperfusi.Hasil: Terdapat penurunan tekanan darah 88/52 mmHg, MAP 62 mmHg, nadi 94x/menit, lalu pasien diberikan support drip Dobutamin 5mcg/kg/menit dan pro rujuk RSUP Dr Sardjito untuk primary PCI ec cardiogenic shock. Berdasarkan pertimbangan adanya syok kardiogenik yang terjadi pada pasien, terapi fibrinolisis tidak dipilih, mengingat hasilnya tidak akan efektif karena rendahnya tekanan aorta. Tekanan aorta yang rendah akan mengganggu pengantaran agen fibrinolisis.Simpulan: STEMI dengan syok kardiogenik menambah kompleksitas klinis pasien. Fibrinolisis tidak efektif pada pasien dengan syok kardiogenik, sehingga primary PCI menjadi modalitas pilihan. Jadi, dapat disimpulkan bahwa syok kardiogenik merupakan kontraindikasi pemberian reperfusi fibrinolisis.